Investment-specific shocks, business cycles, and asset prices - Giuliano Curatola; Michael Donadelli; Patrick Grüning; Christoph Meinerding (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2016)
We introduce long-run investment productivity risk in a two-sector production economy to explain the joint behavior of macroeconomic quantities and asset prices. Long-run productivity risk in both sectors, for which we provide economic and empirical justification, acts as a substitute for shocks to the marginal efficiency of investments in explaining the equity premium and the stock return volatility differential between the consumption and the investment sector. Moreover, adding moderate wage rigidities allows the model to reproduce the empirically observed positive co-movement between consumption and investment growth.
urn:nbn:de:hebis:30:3-395822
Keywords: E32; G12; 330; general equilibrium asset pricing; production economy; long-run risk; investment-specific shocks; nominal rigidities